2007
DOI: 10.1161/circulationaha.106.657627
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Uric Acid and the Metabolic Syndrome Among US Children and Adolescents

Abstract: Background-The association between concentrations of uric acid and the metabolic syndrome in children and adolescents remains incompletely understood. The objective of this study was to examine how these 2 were associated in a nationally representative sample of US children and adolescents. Methods and Results-We performed a cross-sectional analysis of 1370 males and females aged 12 to 17 years using data from the National Health and Nutrition Examination Survey 1999 -2002. The prevalence of the metabolic synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

36
355
3
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(423 citation statements)
references
References 42 publications
36
355
3
12
Order By: Relevance
“…The highest prevalence of MS with increasing levels of UA was also demonstrated by a study carried out by Choi and Ford 16,17 using data from NHANES. In some other studies, such as the one by Coutinho et al 33 and Desai et al 15 , it can be observed that US was associated with components that constitute MS, and the higher the number of components of the syndrome, the higher the association.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The highest prevalence of MS with increasing levels of UA was also demonstrated by a study carried out by Choi and Ford 16,17 using data from NHANES. In some other studies, such as the one by Coutinho et al 33 and Desai et al 15 , it can be observed that US was associated with components that constitute MS, and the higher the number of components of the syndrome, the higher the association.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have demonstrated that UA is an independent risk variable for cardiovascular risk factors [2][3][4][5][13][14][15][16][17][18][19][20][21][22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional MetS criteria, such as those developed for adults by the National Cholesterol Education Program Adult Treatment Panel (ATP-III) 1 or adolescent adaptations, 2 define MetS diagnosis as presence of at least 3 abnormalities among these 5 clinical components. MetS is a priority to characterize because it is a significant risk factor for cardiovascular disease (CVD) and type 2 diabetes mellitus (T2DM).…”
mentioning
confidence: 99%
“…In addition, the findings are also consistent with previous studies in an obese pediatric population whereby in vivo XO activity was increased, as assessed by in vivo caffeine phenotyping strategies 13 ; and high serum uric acid concentrations were associated with metabolic syndrome and CVRs in similar pediatric populations. [14][15][16] We observed that adiponectin was inversely associated with XO activity. This finding is similar to previous studies whereby plasma uric acid concentration (a surrogate for XO activity) was inversely proportional to adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 95%